2019
DOI: 10.31646/gbio.12
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of three key antiviral drugs used to treat orthopoxvirus infections: a systematic review

Abstract: Background: In a global political climate increasingly concerned about terrorism, bioterrorism agents such as smallpox would undoubtedly be catastrophic. Since WHO announced the eradication of smallpox in 1980, consequently discontinuing the worldwide vaccination campaign, today's population is either immunologically naïve or has waning levels of protection. Further, up to 25% of today's population are contraindicated for smallpox vaccination due to various immunodeficiency conditions. The aim of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 104 publications
0
25
0
Order By: Relevance
“…Effective antivirals include tecovirimat and brincidofovir. 13 Cidofovir can also be used but is nephrotoxic. Vaccinia immune globulin is effective but has limited supply.…”
Section: Diagnosis Treatment and Epidemic Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective antivirals include tecovirimat and brincidofovir. 13 Cidofovir can also be used but is nephrotoxic. Vaccinia immune globulin is effective but has limited supply.…”
Section: Diagnosis Treatment and Epidemic Controlmentioning
confidence: 99%
“…Vaccinia immune globulin is effective but has limited supply. 13 Epidemic control includes case finding, isolation of cases, contact tracing and ring vaccination. The risk to contacts is classified according to the kind of exposure and individual risk.…”
Section: Diagnosis Treatment and Epidemic Controlmentioning
confidence: 99%
“…The nephrotoxicity of cidofovir has been removed in the form of CMX-001 [6]. Numerous orthopoxvirus species have shown antiviral effectiveness when exposed to CMX-001 [66]. The medication ST-246 has shown efficacy against a variety of orthopoxvirus species, including the variola virus [66].…”
Section: Therapeutic Medications and Immunisationsmentioning
confidence: 99%
“…Numerous orthopoxvirus species have shown antiviral effectiveness when exposed to CMX-001 [66]. The medication ST-246 has shown efficacy against a variety of orthopoxvirus species, including the variola virus [66]. It prevents the release of the intracellular virus from the cell.…”
Section: Therapeutic Medications and Immunisationsmentioning
confidence: 99%
“…Once diagnosed, treatment for monkeypox is largely supportive and symptomatic. There are no approved therapies for monkeypox but animal studies suggest cidofovir, tecovirimat and brincidofovir may have a role in treatment or lowering disease burden (57). Adler et al have reported successful clinical treatment of human Monkeypox with oral Brincidofovir in three cases -the dosing regimen was 200 mg as a single dose in one case and two doses in the other two cases.…”
Section: Monkeypoxmentioning
confidence: 99%